Investigating the effect of NucleoSpin® Forensic Filters on DNA recovery from swabs - Hitewa, Alina Ndahafa (Division of Forensic Medicine and Toxicology, 2021)
The burden of unresolved crime in South Africa highlights the need to improve methods of identifying perpetrators of crimes. One globally accepted method for human identification is forensic DNA profiling. Since trace evidence is often retrieved in small amounts, the optimal recovery of DNA from these samples is crucial. Methods for the recovery of touch DNA from swabs typically make use of a spin basket or filter, combined with a centrifugation step, to enhance the release of cells from the swab prior to DNA extraction. The NucleoSpin® Forensic Filter (Macherey-Nagel, Düren) is one such example, but it has not been thoroughly assessed on touch DNA samples. This study aimed to assess if the inclusion of the NucleoSpin® Forensic Filter significantly improved DNA recovery and DNA profiling success from cotton and flocked swabs used to collect touch DNA and buccal cells (control). Buccal cells and touch DNA samples were collected from 25 volunteers using each swab type (cotton and flocked) in duplicate. DNA was extracted from the samples using the NucleoSpin® DNA Forensic kit, one set with, and the other set without, NucleoSpin® Forensic Filters. DNA concentration was assessed using Qubit™ fluorometry and qPCR, and DNA profiling was done using the PowerPlex® ESX 16 system. The inclusion of the NucleoSpin® Forensic Filters significantly improved DNA concentration in buccal cells collected using flocked swabs (p = 0.035). However, no significant differences were noted for touch DNA samples, for either swab type. There was also no significant difference in DNA profiling success when NucleoSpin® Forensic Filters were used, regardless of swab and sample type. These results suggest that the NucleoSpin® Forensic Filters should not be included in the DNA extraction workflow, particularly for touch DNA samples. With only 16 % of touch DNA samples yielding full DNA profiles, there is the need to improve DNA recovery. Factors such as swab type and swab preservation buffers, should be investigated in future research.